2005
DOI: 10.1007/s00167-005-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment of the hip in early and midstage degenerative joint disease

Abstract: The purpose of this study was to present the technique of arthroscopic capsule release in patients with early and midstage degenerative joint disease of the hip. In 22 patients we performed an arthroscopic capsular release of the hip joint capsule with simultaneous synovectomy and percutaneous drilling of areas of bone edema. The age of the patient ranged from 28 to 65 years (mean 52 years). There were 14 male and 8 female patients. All patients had suffered from a significant reduction of quality of life. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
(32 reference statements)
2
19
0
Order By: Relevance
“…The mean time interval for mild OA was 2.2 years (range, 0.2-5 years) whereas for severe OA it was 1.1 years (range, 0.1-5.1 years). These findings correlate with previous publications on short term results [3-6]. In addition, Margheritini and Villar [5] showed that young patients with early OA were those associated with a higher rate of procedure success, similar to our observation of longer time intervals to THA in patients younger than 55.…”
Section: Discussionsupporting
confidence: 92%
“…The mean time interval for mild OA was 2.2 years (range, 0.2-5 years) whereas for severe OA it was 1.1 years (range, 0.1-5.1 years). These findings correlate with previous publications on short term results [3-6]. In addition, Margheritini and Villar [5] showed that young patients with early OA were those associated with a higher rate of procedure success, similar to our observation of longer time intervals to THA in patients younger than 55.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, Horisberger et al reported a 60% (12 patients) failure rate using non-arthritic hip score (NAHS) in 20 patients with radiographic OA (Tonnis Grades 1-3) at a mean last followup of 3 years [14]. Most studies evaluating hip arthroscopy in the setting of OA predate FAI bony resections [4,8,13,17,18,23,27,35] ( Table 6). Margheritini and Villar [23] evaluated 133 patients with hip OA who underwent hip arthroscopy and reported a 39% failure rate at a mean followup of 18 months using the HHS.…”
Section: Discussionsupporting
confidence: 86%
“…Studies show that the presence of OA negatively impacts outcomes after hip arthroscopy and nonarthroplasty open hip surgery [2,4,8,13,14,17,18,23,25,27,[29][30][31][32]35]. However, most studies predate FAI correction, are limited to small numbers, or lack well-defined independent predictors of improved function or failure rates after managing FAI in the presence of OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this level of evidence study a successful outcome rate of 89% is reported. Jerosch et al 4 . showed good to excellent outcome results in 82% of a case series.…”
Section: Introductionmentioning
confidence: 96%